Hamemayu Hayuning Nagara: A Bibliometric Analysis of the Policy on Increasing the Value Added Tax Rate as a Means of Welfare and Social Justice - Kusumastuti, Dinda Amelia; Prajnasari, Puspa Ratri; Wardani, Pramita Sukma (Westscience Press, 2026)
This study analyzes developments in Value Added Tax (VAT) research in developing countries using a bibliometric approach and relates them to the Javanese philosophy of Hamemayu Hayuning Nagara, which emphasizes harmony between state interests and public welfare. Bibliometric data were obtained from the Scopus database for the 2014–2024 period, comprising 856 selected articles. The analysis was conducted through keyword mapping, author and country collaboration networks, co-citation analysis, document coupling, and thematic mapping using Biblioshiny in RStudio. The results show that the global VAT discourse is dominated by themes such as tax reform, value-added tax, and fiscal policy, with an increasing shift of focus toward issues of equity, redistribution, poverty, and inequality. The findings indicate that VAT is not merely a fiscal instrument, but also a tool of social and economic intervention used by governments to promote equity and achieve social justice. In the case of Indonesia, the increase of the VAT rate to 12% needs to be positioned within a framework of protecting vulnerable groups, ensuring fiscal transparency, and enhancing the effectiveness of social policies. Through the Javanese philosophy of Hamemayu Hayuning Nagara, an ideal VAT policy is understood as an effort to balance the need for state revenue with the moral obligation to safeguard public welfare. This study contributes by providing an intellectual map of VAT research and offering an ethical perspective based on local wisdom for the formulation of fair and sustainable tax policies